Relationship Between Left Ventricular Ejection Fraction Variation and Systemic Vascular Resistance: A Prospective Cardiovascular Magnetic Resonance Study - Mandry, Damien; Girerd, Nicolas; Lamiral, Zohra; Huttin, Olivier; Filippetti, Laura; Micard, Emilien; Beaumont, Marine; Ncho Mottoh, Marie-Paule Bernadette; Pace, Nathalie; Zannad, Faïez; Rossignol, Patrick; Marie, Pierre-Yves (Frontiers in Cardiovascular Medicine, 2021)
Introduction: This cardiovascular magnetic resonance (CMR) study aims to determine whether changes in systemic vascular resistance (SVR), obtained from CMR flow sequences, might explain the significant long-term changes in left ventricular (LV) ejection fraction (EF) observed in subjects with no cardiac disease history. Methods: Cohort subjects without any known cardiac disease but with high rates of hypertension and obesity, underwent CMR with phase-contrast sequences both at baseline and at a median follow-up of 5.2 years. Longitudinal changes in EF were analyzed for any concomitant changes in blood pressure and vascular function, notably the indexed SVR given by the formula: mean brachial blood pressure / cardiac output x body surface area. Results: A total of 118 subjects (53±12 years, 52% women) were included, 26% had hypertension, and 52 % were obese. Eighteen (15%) had significant EF variations between baseline and follow-up (7 increased EF and 11 decreased EF). Longitudinal changes in EF were inversely related to concomitant changes in mean and diastolic blood pressures (p=0.030 and p=0.027, respectively) and much more significantly to SVR (p<0.001). On average, these SVR changes were -8.08±9.21 and +8.14±8.28 mmHg.min.m2.L-1 respectively in subjects with significant increases and decreases in EF, and 3.32±7.53 mmHg.min.m2.L-1 in subjects with a stable EF (overall p<0.001). Conclusions: Significant EF variations are not uncommon during the long-term CMR follow-up of populations with no evident health issues except for uncomplicated hypertension and obesity. However, most of these variations are linked to SVR changes and may therefore be unrelated to any intrinsic change in LV contractility. This underscores the benefits of specifically assessing LV afterload when EF is monitored in populations at risk of vascular dysfunction. Clinical Trial Registrations - NCT01716819 and NCT02430805 on the ClinicalTrials.gov site.